March Test for Static Neighborhood Pattern-Sensitive Faults in Random-Access Memories - Huzum, C.; Cascaval, P. (Elektronika ir Elektrotechnika, 2012)
A multibackground March test (March-76N) for a model of static neighborhood pattern sensitive faults (NPSFs) in N ´ 1 random-access memories is presented. March-76N is able to cover both simple and linked NPSFs. As any other test dedicated to the NPSFs, March-76N assumes that the storage cells are arranged in a rectangular grid and the mapping from logical addresses to physical cell locations is known completely. With a length of 76N, this March test is more efficient than other published tests dedicated to this model. Ill. 4, bibl. 16, tabl. 4 (in English; abstracts in English and Lithuanian). DOI: http://dx.doi.org/10.5755/j01.eee.119.3.1369